LINGKUNGAN BISNIS, ORIENTASI KEWIRAUSAHAAN, ORIENTASI PASAR, DAN KINERJA USAHA MIKRO, KECIL DAN MENENGAH - Maria Pampa Kumalaningrum (Fakultas Bisnis Universitas Kristen Duta Wacana, 2012)
ABSTRACT This study examined the effect of environmental factors, entrepreneurial orientation, and market orientation on profitability in small business. In this study, we consider two dimensions of external environment: technological turbulence and competitive intensity. Theoretically, technological turbulence, competitive intensity, and entrepreneurial orientation are correlated, but distinct construct. Data was processed with Structural Equation Modeling using AMOS program. The results showed that technological turbulence has no direct effect on market orientation, but competitive intensity proved to have significant impact on market orientation. Entrepreneurial orientation has a direct effect and an indirect effect on profitability mediated by market orientation. The result also showed that market orientation proved to have significant impact on profitability. Based on the results, this study suggest, at least in small firms, competitive intensity and entrepreneurial orientation complements market orientation by instilling an opportunistic culture that impacts the profitability. Keywords: technological turbulence, competitive intensity, entrepreneurial orientation, market orientation, and profitability.